2009
DOI: 10.1186/1476-7120-7-53
|View full text |Cite
|
Sign up to set email alerts
|

Functional measurements based on feature tracking of cine magnetic resonance images identify left ventricular segments with myocardial scar

Abstract: BackgroundThe aim of the study was to perform a feature tracking analysis on cine magnetic resonance (MR) images to elucidate if functional measurements of the motion of the left ventricular wall may detect scar defined with gadolinium enhanced MR.Myocardial contraction can be measured in terms of the velocity, displacement and local deformation (strain) of a particular myocardial segment. Contraction of the myocardial wall will be reduced in the presence of scar and as a consequence of reduced myocardial bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 31 publications
2
87
4
2
Order By: Relevance
“…The technique can be applied for the quantification of right and left ventricular (LV) systolic and diastolic function using strain 10,18 and SR 19 imaging as well as myocardial torsion and diastolic recoil quantification. 20,21 The study of atrial physiology using strain and SR imaging has recently been explored.…”
Section: Quantitative Assesment Of Cardiovascular Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The technique can be applied for the quantification of right and left ventricular (LV) systolic and diastolic function using strain 10,18 and SR 19 imaging as well as myocardial torsion and diastolic recoil quantification. 20,21 The study of atrial physiology using strain and SR imaging has recently been explored.…”
Section: Quantitative Assesment Of Cardiovascular Physiologymentioning
confidence: 99%
“…The majority of CMR-FT studies have used the Diogenes and Cardiac Performance Analysis-MR software provided by TomTec Imaging systems (TomTec, Unterschleissheim, Germany). 10 Other vendors including Toshiba 11 (Tokyo, Japan) and more recently Circle 12 (Calgary, Canada) have released alternative FT software platforms. The purpose of this article is to summarize the basic principles, evolving clinical applications, accuracy and reproducibility data of CMR-FT.…”
mentioning
confidence: 99%
“…-16 -shown that measurements of velocity, displacement and peak systolic strain in the radial direction by MRI were able to differentiate segments with varying extent of scar (14). The most accurate information was obtained by measurements of radial strain in that study.…”
Section: Discussionmentioning
confidence: 64%
“…Most of these methods depend on texture features to track predefined points on the inner and outer LV wall. For example, Maret et al [94] used a feature tracking method to estimate the strain and other indexes from cine CMRI and showed that it can be used for the detection of the transmural scar. Hor et al [95] correlated between the estimated strains from tagged MRI (using HARP method) and from cine CMRI (using tracking) in a population with a wide range of cardiac dysfunction.…”
Section: Functional Strainmentioning
confidence: 99%
“…To avoid the inter-slice variability, recent trends estimate the strain from cine CMRI (e.g., [94][95][96][97]). Most of these methods depend on texture features to track predefined points on the inner and outer LV wall.…”
Section: Functional Strainmentioning
confidence: 99%